Moderat Antar Umat, Pendidikan, dan Organisasi di Indonesia - Tatang Muh Nasir; Opik Taufik Kurahman (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2023)
The moderate stance taken by religious, educational and organizational groups is discussed in this article. This study used a literature review, and moderate was defined either explicitly or implicitly. The word "moderate" means "moderate", but it also has the implication "a person who agrees to be reasonable", as in "he always finds a middle way to deal with the problems he faces". Finding the middle ground requires maintaining a positive attitude and putting the needs of others before your own. But calm, harmony, no conflict, and modernity is what these people want. Every aspect, including structure and instructions, requires moderation.